Implementation and Operational Research: Linkage to Care Among Methadone Clients Living With HIV in Dar es Salaam, Tanzania. - Tran, Olivia C; Bruce, Robert Douglas; Masao, Frank; Ubuguyu, Omary; Sabuni, Norman; Mbwambo, Jessie; Lambdin, Barrot H (Journal of acquired immune deficiency syndromes (1999), 2015)
The first methadone maintenance treatment clinic in Tanzania was launched in February 2011 to address an emerging HIV epidemic among people who inject drugs. We conducted a retrospective cohort study to understand factors associated with linkage to HIV care and explore how a methadone maintenance treatment clinic can serve as a platform for integrated HIV care and treatment.
Keywords: Adult; Female; Health Services; HIV Infections; Humans; Male; Methadone; Opiate Substitution Treatment; Substance Abuse, Intravenous; Tanzania